Complex Networks of Prion-Like Proteins Reveal Cross Talk Between Stress and Memory Pathways in Plants - Garai, Sampurna; Citu,; Singla-Pareek, Sneh L.; Sopory, Sudhir K.; Kaur, Charanpreet; Yadav, Gitanjali (Frontiers in Plant Science, 2021)
Prions can be considered as molecular memory devices, generating reproducible memory of a conformational change. Prion-like proteins (PrLPs) have been widely demonstrated to be present in plants, but their role in plant stress and memory remains unexplored. In this work, we report the widespread presence of PrLPs in plants through a comprehensive analysis of 39 genomes representing major taxonomic groups. We find diverse functional roles associated with these proteins in various species, and we term the entire PrLP complement of a genome, as its ‘Prionome’. Investigation of rice transcriptomic datasets further delineated the role of PrLPs in stress and developmental responses, leading us to explore whether and to what extent PrLPs may build stress memory. We found the rice prionome to be significantly enriched for Transposons/Retrotransposons (Ts/RTRs), and superimposed it with the corresponding interactome, regulome and diurnal transcriptomes. Regulatory inferences derived from superimposition of these datasets revealed a complex network and crosstalk between PrLPs, transcription factors and genes known to be involved in stress priming. This integrative meta-analysis connects transient and trans-generational memory mechanisms in plants with prion-like proteins, suggesting that plant memory may rely upon protein-based signals in addition to chromatin-based epigenetic signals. We derive transcriptional regulatory inferences from the rice diurnal gene expression profiles to identify specific prion-like genes that may be memory hubs in rice. Taken together, our work provides important insights into the anticipated role of prion-like candidates in stress and memory, paving the way for more focussed studies for validating role of identified PrLPs in memory acclimation.